Kenaf patch repair for composite parts and damage identification strategy - Muda, Mohd Khairul Hafiz (2015)
Occasionally, fatigue cracks and damages are found to have developed along rivet holes and other highly stresses regions of aircrafts. In order to extend the life of these aircrafts, repairs should be made to arrest these cracks. Patch repair promotes an innovative repair technique, which can enhance the way in which aircrafts are being maintained. Such repairs generally have one of three objectives which are crack enhancement, crack patching or corrosion repair. Repair of cracked structure may be performed by bonding an external patch to the structure, to either halt or slow the crack growth proposition. Materials that used to repair the structure must be able to withstand the expected conditions in the damaged area. Natural fiber is one of materials or composites that have the potential to be used in the composites approach for aircraft parts. Natural fibers offer both cost saving and a reduction in density when compared to other fibers. Though the strength of natural fiber is not as great as glass, the specific properties are comparable and can be the patching component. The research has been done to find the suitability of natural fiber Kenaf, Hibiscus Cannabinus to be the part of potential material for patching repair. The acquired result was analyzed accordance with real application and the final properties were determined whether it satisfies the requirement such as high strength and stiffness, fatigue and environmental durability and formability, and also long-term durability of the patch. From experimental results, the compressive strength for kenaf patch repair panel is almost the same with undamaged panel and putty patch repair panel which are 230.08GPa, 230.41GPa and 230.47GPa. Meanwhile, the tensile strength for kenaf patch repair panel is slightly less than undamaged panel but higher than putty patch repair panel which are 725.94GPa, 874.07GPa and 672.68GPa. Hence, Kenaf fibre materials have great potential to be used as patch repair for composite parts. For damage detection strategy for the repair, the use of PZT sensors for Structural Health Monitoring (SHM) systems provided a continuous active monitoring on the panels. The specimens with bonded PZT sensors were subjected to mechanical testing. An online and active SHM monitoring was carried out during the compression and tensile testing. During this active sensing, the specimens showed different wave pattern from the elastic region to the specimen failure. A repaired specimen showed same signal behaviour with undamaged specimen. This is important since a new baseline of detecting new damage need to be established for the new monitoring to take place.